Pengaruh Kepemimpinan Kepala Sekolah terhadap Peningkatan Kualitas Pendidikan Islam di MIN 15 Aceh Besar - Nuhari, Insan; Zakaria, Zakaria; Jalaluddin, Jalaluddin; Azwir, Azwir (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
A study entitled "The Influence of Principal Leadership on Improving the Quality of Islamic Education at MIN 15 Aceh Besar" has been conducted. This study aims to implement the leadership style of the principal at MIN 15 Aceh Besar in the context of Islamic education, to determine the obstacles faced by the principal in carrying out his leadership role to improve the quality of Islamic education at MIN 15 Aceh Besar, and to determine the perceptions of teachers, students, and parents regarding the influence of principal leadership on the quality of Islamic education at MIN 15 Aceh Besar. This study was conducted at MIN Aceh Besar using a qualitative approach. Data collection techniques were carried out through: (1) In-depth interviews; (2) Participatory observation and (3) documentation. The selection of research informants used purposive techniques combined with "Snowball sampling". Based on the results of the study, Principal leadership is a key factor that determines the quality of education in schools, so that the education process can run in a planned, systematic, and professional manner. The principal in carrying out his leadership in managing the school must pay attention to improving the quality of teachers. This is because teachers are the ones who deal directly with students. Improving the quality of teachers will have an impact on student achievement. Therefore, a qualified principal will always invite, persuade, lead, guide, and encourage teachers to teach professionalism in order to achieve educational goals. However, in reality, the principal’s leadership has not been running well to create a good learning process and quality of education.